المعايير الوراثية لبعض الصفات الكمية في ثلاثة هجن من الذرة الصفراء - معلا, محمد; حسيان, رامز; الأحمد, سمير (Latakia University Journal -Biological Sciences Series, 2013)
أُجريت هذه الدراسة في مركز بحوث حمص خلال المواسم الزراعية 2008, 2009 و2010 بهدف دراسة طبيعة الفعل الوراثي وتعبيره, درجة السيادة, قوة الهجين ومقدار الانخفاض في التربية الداخلية.زرعت حبوب العشائر الستة لثلاثة هجن منتخبة في تجربة بتصميم القطاعات كاملة العشوائية في ثلاثة مكررات.أظهرت نتائج تحليل التباين فروقاً معنوية بين عشائر الهجن لكل الصفات المدروسة، وكانت قيم قوة الهجين موجبة ومعنوية قياساً بمتوسط الأبوين والأب الأفضل في كل الهجن لمعظم الصفات. تخطت درجة السيادة +1 في كل الصفات عدا ارتفاع العرنوس وهذايشير إلى السيادة الفائقة. وبينت النتائج حدوث تدهور معنوي في الهجين1 لمعظم الصفات بينما كان غير معنوياً في الهجينين 2و3 لكل الصفات باستثناء ارتفاع النبات،وغلة النبات الفردي في الهجين3. احتل الفعل الوراثي التفوقي من النمط سيادي×سيادي (l) للهجين1 والفعل الوراثي السيادي(h) للهجينين2و3 المرتبة الأولى في التحكم بوراثة صفة ارتفاع النبات. وسيطر النمط سيادي×سيادي (l) للهجين2و1و السيادي(h) للهجين3 على وراثة صفة ارتفاع العرنوس. وتحكم النمط سيادي×سيادي (l) في وراثة عدد الصفوف بالعرنوس للهجين 1 بينما تحكم الفعل الوراثي التراكمي (d) والسيادي(h) للهجينين 2و3 على الترتيب في وراثة هذه الصفة. وتحكم التراكمي (d), السيادي (h) والتفوقي من النمط تراكمي×سيادي (j) للهجن1و2و3 على الترتيب في وراثة صفة عدد الحبوب بالصف. احتل السيادي (h) المرتبة الأولى في التحكم بوراثة صفة وزن 100 حبة للهجن الثلاثة. وسيطر التراكمي (d) للهجين1 والسيادي (h) للهجينين2و3 في وراثة صفة غلة النبات الفردي. Six population seeds of three yellow maize hybrids were formed at Agricultural Research Center, Homs, during 2008 and 2009 growing seasons. Their plants were evaluated in 2010. The present work aims to determine the genetic parameters in six populations )P1, P2, F1, F2, BC1, and BC2). Mean square results showed significant differences among mean values for all traits in all crosses. Significant heterosis values were positive and relative comparing to mid and better parent for most traits. The potence ratios exceeded (+1) in all traits and crosses except ear height, indicating thus over-dominance. In breeding, depression values were significant in most traits for Cross-1, while their values were non- significant in all traits for Cross-2 except plant height, and also in Cross-3 except plant height and grain yield per plant. In most traits epestasis or dominance gene action occupied the first rank in the genetic effects in order of importance to cross, with the exception of number of rows per ear, number of kernels per row and grain yield per plant where additive gene action occupied the first rank for Cross-2 and Cross-1 respectively. Therefore, it could be suggested that selection for most studied traits in the subsequent generations will be relatively more effective than in the early generations.